Bioaccumulation of trace metals and speciation of copper and zinc in Pacific oysters (Crassostrea gigas) using XANES/EXAFS spectroscopies. (February 2021) - Kunene, Sikhumbuzo Charles; Lin, Kuen-Song; Mdlovu, Ndumiso Vukile; Shih, Wei-Cheng
Abstract: Copper (Cu) and zinc (Zn) concentrations in oyster soft tissues can be particularly high due to contamination, leading to extremely green/blue colors. This raises key questions regarding the behavior and speciation of trace metals in oyster soft tissues. This study investigated trace metal concentration profiles of contaminated Pacific oyster ( Crassostrea gigas ) soft tissues collected from trace metal-contaminated coastal area of Xiangshan District using inductively coupled plasma optical emission spectrometry (ICP-OES), energy dispersive X-ray (EDX), Fourier-transform infrared spectroscopy (FTIR), and X-ray photoelectron spectroscopy (XPS). Moreover, Cu and Zn speciation in contaminated and non-contaminated oyster soft tissues were investigated by X-ray absorption near edge structure spectroscopy/extended X-ray absorption fine structure (XANES/EXAFS) spectroscopic methods. The contents of Cu (1, 100–1, 400 mg/kg) and Zn (500–700 mg/kg) dry weight were high in oyster soft tissue samples. The XANES/EXAFS results revealed that Cu and Zn existed primarily as copper (II) oxide (CuO) and zinc oxide (ZnO) in contaminated oysters. Furthermore, Cu and Zn formed clusters with Cu–O and Zn–O interatomic distances of 1.97 and 2.21 Å, (coordination numbers 1.0 and 5.6), respectively. In non-contaminated oysters, the less abundant Cu and Zn existed mainly as copper(I) sulfide (Cu2 S) and zinc sulfide (ZnS) forming clusters with Cu–S and Zn–S (thiolates) bond distances of 2.09 and 1.23 Å (coordination numbers of 4.6 and 2.4). These results provide further understanding on the chemical speciation of Cu and Zn in contaminated and non-contaminated oyster soft tissues as well as the bioaccumulation of trace metals in the oyster soft tissues. Graphical abstract: Image 1 Highlights: Concentration and speciation of Cu and Zn was investigated in oyster soft tissues. High Cu and Zn concentrations were detected in green/blue-colored oyster tissues. Cu species existed in tissue mainly as CuO, ZnO, Cu2S, and ZnS identified by XANES. Cu–O, Zn–O, Cu–S, and Zn–S interatomic distances were 1.97, 2.21, 2.09, and 1.23 Å. Discharge of toxic metals from high-tech industrial park was confirmed.